Lithospheric mantle evolution monitored by overlapping large igneous provinces: case study in southern Africa - Jourdan, Fred; Bertrand, H.; Fraud, G.; Le Gall, B.; Watkeys, M. K. (Elsevier Science BV, 2009)
Most of the studies on the large igneous provinces (LIPs) focus on Phanerozoic times, and in particular, thoserelated to the disruption of Pangea (e.g. CAMP, Karoo, Parana–Etendeka) while Precambrian LIPs (e.g.Ventersdorpf, Fortescue) remain less studied. Although the investigation of Precambrian LIPs is difficultbecause they are relatively poorly preserved, assessment of their geochemical characteristics in parallel withyounger overlapping LIP is fundamental for monitoring the evolution of the mantle composition through time.Recent 40Ar/39Ar dating of the Okavango giant dyke swarm (and related sills) in southern Africa showed that~90% of the dykes were emplaced at 179±1Ma and belong to the Karoo large igneous province whereas ~10% ofdykes yielded Proterozoic ages (~1–1.1 Ga). Here,weprovide newmajor, trace and rare earth elements analysesof the low-Ti Proterozoic Okavango dyke swarm (PODS) that suggest, combined with age data, a cognate originwith the 1.1 Ga Umkondo large igneous province (UIP), southern Africa.The geochemical characteristics of the PODS and UIP basalts are comparable to those of overlapping low-TiKaroo basalts, and suggest that both LIPs were derived from similar enriched mantle sources. A mantle plumeorigin for these LIPs is not easily reconciled with the geochemical dataset and the coincidence of twocompositionally similar mantle plumes acting 900 Myr apart is unlikely. Instead,we propose that the Umkondoand Karoo large igneous provinces monitored the slight evolution of a shallow enriched lithospheric mantlefrom Proterozoic to Jurassic.